Hydrocarbon pollutants shape bacterial community assembly of harbor sediments. Issue 1 (15th March 2016) - Barbato, Marta; Mapelli, Francesca; Magagnini, Mirko; Chouaia, Bessem; Armeni, Monica; Marasco, Ramona; Crotti, Elena; Daffonchio, Daniele; Borin, Sara
Abstract: Petroleum pollution results in co-contamination by different classes of molecules, entailing the occurrence of marine sediments difficult to remediate, as in the case of the Ancona harbor (Mediterranean Sea, Italy). Autochthonous bioaugmentation (ABA), by exploiting the indigenous microbes of the environment to be treated, could represent a successful bioremediation strategy. In this perspective we aimed to i) identify the main drivers of the bacterial communities' richness in the sediments, ii) establish enrichment cultures with different hydrocarbon pollutants evaluating their effects on the bacterial communities' composition, and iii) obtain a collection of hydrocarbon degrading bacteria potentially exploitable in ABA. The correlation between the selection of different specialized bacterial populations and the type of pollutants was demonstrated by culture-independent analyses, and by establishing a collection of bacteria with different hydrocarbon degradation traits. Our observations indicate that pollution dictates the diversity of sediment bacterial communities and shapes the ABA potential in harbor sediments. Highlight: Pollution by hydrocarbons and heavy metals drives sediment bacterial diversity. Marinobacter and Alcanivorax are main players of alkane degradation in the sediments. The isolated bacteria show biotechnological traits exploitable for bioremediation.